Upgrading Community’s Dried Flower Products as Souvenirs and Decorative from Community Capital at Din Thong Sub-district, Phitsanulok Province - Kaewsritong, Jiraphat; Srithawirat, Thunwadee; Sornnoey, Keeratiya; Intakan, Wirachya; Siwnguan, Kunchaya (Area Based Development Research Journal, 2019)
This research aims to develop a community’s dried flower products to be certified by Thai community product standards and to transfer knowledge and technology of dried fresh flower production to the target communities in Din Thong sub-district, Wang Thong district, Phitsanulok province. This study focuses on the implementation of community participation. Scopes for conducting the study include 1) survey of the community context, physical information, social capital, local wisdom, problems, and demand, 2) development of products to be certified by community product standards, 3) transfer of knowledge and technology through workshops and 4) marketing. Targets of this study consist of 40 people including the locals, community leaders, community development officers, and stakeholders. Data are collected through group meeting participation, observation, and interviews. Tools in this study are questionnaires and interview forms. The results shows that Din Thong community has formed and registered as a new career group. Their value added dried fresh flowers produced from local resources are certified by Thai community product standards. From the workshops, the participants reveal high levels of satisfaction in project participation and ability to learn and practice accordingly. For marketing, the products are available for sale at stores in provincial tourist attraction sites, and the social media channel as Facebook page “Sattri Sri Din Thong Group” is also open for online business. This product can generate additional revenue for the community.